Existentialism And Spirituality (Existential Analysis: Journal of the Society for Existential Analysis, 2018)
This paper attempts to examine the question as to whether there is such a thing as existential spirituality. Emmy van Deurzen has postulated that there is: in addition to the well-established categories of the Umwelt, the Mitwelt and the Eigenwelt she has urged that we should also consider the Uberwelt – the spiritual world. However, she has said very little about this realm and the present paper attempts to put some flesh on the bones.
Keywords: Spirituality, existentialism; transpersonal; Uberwelt; awareness